2009
DOI: 10.1128/jvi.00308-09
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Hepatitis C Virus Subgenomic Deletion Mutants Replicate Efficiently in Huh-7 Cells and Are trans -Packaged In Vitro To Generate Infectious Defective Particles

Abstract: Naturally occurring hepatitis C virus (HCV) subgenomic RNAs have been found in several HCV patients. These subgenomic deletion mutants, mostly lacking the genes encoding envelope glycoproteins, were found in both liver and serum, where their relatively high abundance suggests that they are capable of autonomous replication and can be packaged and secreted in viral particles, presumably harboring the envelope proteins from wild type virus coinfecting the same cell. We recapitulated some of these natural subgeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 56 publications
2
49
0
Order By: Relevance
“…Steinmann and coworkers showed previously that the luciferase-tagged JFH1 genome lacking the envelope-encoding regions alone could be rescued by a helper virus expressing the entire JFH1 genome, but virus production was low as determined by the luciferase assay, and it was not certain whether this virus lacking the envelopeencoding regions alone was able to expand and propagate in packaging cells, although these investigators did show that an HCV subgenomic replicon could be trans-complemented and that the viruses produced could be passaged in the packaging cell line that expressed all HCV structural proteins (47). Moreover, Pacini and coworkers showed that the envelope genedeleted J6/JFH1 RNA could be rescued by the full-length J6/JFH1 genome or by the regions encoding the entire structural proteins (core-NS2) in trans, but not by the expression of envelope proteins alone in trans (40). During the revision of this article, Bianchi and colleagues also showed that the a E1E2-deficient JFH1 genome could be rescued by a packaging cell line expressing autologous envelope proteins (6).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Steinmann and coworkers showed previously that the luciferase-tagged JFH1 genome lacking the envelope-encoding regions alone could be rescued by a helper virus expressing the entire JFH1 genome, but virus production was low as determined by the luciferase assay, and it was not certain whether this virus lacking the envelopeencoding regions alone was able to expand and propagate in packaging cells, although these investigators did show that an HCV subgenomic replicon could be trans-complemented and that the viruses produced could be passaged in the packaging cell line that expressed all HCV structural proteins (47). Moreover, Pacini and coworkers showed that the envelope genedeleted J6/JFH1 RNA could be rescued by the full-length J6/JFH1 genome or by the regions encoding the entire structural proteins (core-NS2) in trans, but not by the expression of envelope proteins alone in trans (40). During the revision of this article, Bianchi and colleagues also showed that the a E1E2-deficient JFH1 genome could be rescued by a packaging cell line expressing autologous envelope proteins (6).…”
Section: Discussionmentioning
confidence: 97%
“…Mutations in NS5A domain III disrupting virus production could be rescued by a helper replicon expressing functional NS5A (3). HCV subgenomic replicon RNA lacking the entire region encoding the structural proteins could produce infectious viruses upon expression of the structural proteins in trans from helper viruses, stably expressing cell lines, or transient plasmid transfection (1,22,33,40,47). However, complementation of HCV with a deletion of the envelope gene by envelope glycoproteins provided alone in trans has not been reported yet.…”
mentioning
confidence: 99%
“…This early expression from input RNA was not seen with Jc1/GLuc2A (Fig. 1), which could reflect the interference of HCV translation by the viral structural genes (11,56,67,70). Since the NS4A F48A replication defect was initially identified in Jc1/GLuc2A, we tested whether the NS4B I7F suppressor could restore replication of a full-length HCV genome.…”
Section: Resultsmentioning
confidence: 99%
“…To better clarify the role of NS4A in virus assembly, we tried to identify second-site mutations that suppressed these defects. We took advantage of the fact that HCV subgenomes can be packaged in trans (1,56,63) to select for trans-packaged replicons containing mutations of interest. This strategy yielded a mutation in NS3 (Q221L) that fully restored assembly of the NS4A K41 mutant in cis and in trans, but did not suppress the assembly defects of other NS4A mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments to elucidate the role of mannose trimming of N-glycans in the HCV life cycle are currently under way. It has recently been demonstrated that subgenomic replicons or defective genomes of HCV that have the potential of translation and self-replication can be encapsidated into infectious viruslike particles by trans-complementation of the viral structural proteins (1,17,32,41,44). In these studies, the viral RNAs were generally generated by in vitro transcription from linearized corresponding plasmids, followed by electroporation into the cells.…”
Section: Discussionmentioning
confidence: 99%